Changing fertility preferences one migrant at a time: the impact of remittances on the fertility rate - George S. Naufal; Carlos Vargas-Silva (Institute for the Study of Labor (IZA), 2009)
In this article we study the relationship between workers' remittances and fertility rate of the remittance receiving country. We identify two main channels by which remittances transfers affect fertility. First, migrants may adopt and later transmit to the household the ideas, values and attitudes predominant in the host country. Arguably, migrants with more attachment to the household would be more inclined to remit money home. Therefore, remittances can be seen as a proxy for the level of social norms (including fertility preferences) that is transmitted from the migrant to the household. Second, previous studies have shown that remittances money is often used for health services and educational expenses, factors that may ultimately decrease fertility rates. Using panel data for several countries we find a negative relationship between remittances and the fertility rate. The relationship is robust for a sub-sample of Latin American and African countries, but not for a sub-sample of Asian countries. In addition to finding evidence on the transfer of social norms from migrants to the home country, the paper also confirms that several socio-economic factors such as female labor force participation, percent of the population in rural areas and GDP per capita affect fertility rates.
urn:nbn:de:101:1-20090327369
Keywords: F22; F24; J13; Q56; 330; Remittances; fertility rate; panel data; Latin America; Africa; Asia; Rücküberweisung (Migranten); Soziale Werte; Privater Haushalt; Fruchtbarkeit; Welt; Lateinamerika; Afrika; Asien